The parable of the persistent widow and the unjust judge: A replica of the suffering of widows in Zimbabwe - Mundenda, Dzikamai; van Eck, Ernest (Verbum et ecclesia, 2021)
This article proposes an alternate way of reading the parable of Jesus with special emphasis on Luke 18:1-8. The goal of this contextual reading is the search for the liberation of the violated and disenfranchised widows in independent Zimbabwe. In the reading of the parable, the sociocultural and historical context of Luke is used for an informed reading and analysis of the characters and the plot of the parable. This reading is then compared with the contemporary sociocultural and historical context of widows in the independent Zimbabwe. It is argued that the Lukan socio-cultural and historical contexts provided the source and reason for the persistence and courage for the persistent widow, and that the widows in independent Zimbabwe must follow the example of the persistent widow to curb disenfranchisement and violations in their own context. Intradisciplinary and/or interdisciplinary implications The article indicates that the persistent widow in the parable can be seen as a model for courage and persistence for the suffering widows in Zimbabwe. This model can chart a new course for widows who daily suffer injustice in Zimbabwe because of its patriarchal cultural setting.